Vascular and Nonvascular Interventions in Gynecology - Banday, Showkat A.; Gopinathan, Kiran; Poyyamoli, Santhosh; Dev, Bhawna (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Advancements in radiology have revolutionized medicine, making image-guided procedures the standard of care due to their precision and minimally invasive nature. In gynecology, these interventions are classified into nonvascular and vascular procedures. Nonvascular interventions include diagnostic biopsies and therapeutic procedures such as high-intensity focused ultrasound, radiofrequency ablation (RFA), microwave ablation (MWA), cryoablation (CA), and sclerotherapy. Vascular interventions are primarily therapeutic, including uterine artery embolization (UAE), gonadal vein embolization (GVE), and iliac/renal vein stenting.Nonvascular interventions can be performed via transabdominal, transvaginal, or transrectal routes under ultrasound guidance, or transabdominal or transgluteal routes under computed tomography guidance. Biopsies are used to evaluate complex adnexal masses, while aspiration and drainage procedures manage ovarian cysts and pelvic collections. Sclerotherapy is an alternative to laparoscopic cystectomy for ovarian endometriomas, and RFA, MWA, and CA are used for uterine fibroids and hepatic metastasis in ovarian malignancies.Vascular interventions, such as UAE, are effective for treating uterine fibroids and adenomyosis, offering a minimally invasive alternative to surgery. UAE reduces fibroid size and alleviates symptoms, with a high success rate. UAE is moderately effective in providing symptomatic relief in adenomyosis for patients who desire to preserve the uterus. Embolization is also used for managing bleeding in gynecological malignancies and treating pelvic venous disease (PeVD). GVE and pelvic varicosities sclerotherapy are effective for PeVD, while venous stenting addresses vein compression.Image-guided interventions provide safe and effective diagnostic and therapeutic options for various gynecological conditions, improving patient outcomes and preserving fertility.
Keywords: gynecology; interventional radiology; interventions; nonvascular; vascular